PENGARUH PENGALAMAN KERJA, LINGKUNGAN KERJA, DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGMENT - I Gusti Agung Diah Dwi Jayanti; Luh Kade Datrini; Ni Luh Putu Mita Miati (Faculty of Economics and Business, Universitas Warmadewa, 2025)
Audit judgment is the auditor's policy in assessing the results of the examination that affect the fairness offinancial statements. Numerous cases related to audit judgment by the Supreme Audit Agency (BPK)haveraised doubts among users of BPK audit reports. The differing results found by previous researchers have ledto inconsistencies in research and a lack of studies investigating the influence of the work environment onaudit judgment. Therefore, researchers see an opportunity to re-examine the factors that influence auditjudgment. This study aims to identify the influence of work experience, work environment, and time budgetpressure on audit judgment among BPK auditors in Bali Province. Data were collected through a survey of50 BPK auditors in Bali Province. The sampling method used was non-probability sampling with a purposivesampling technique, and the analysis was conducted using Structural Equation Model (SEM) with theSmartPLS analysis tool. The results of the study indicate that the work experience variable has a significantpositive influence on audit judgment. However, the work environment and time budget pressure variables donot have a significant influence on audit judgment. This study has theoretical and practical implications forthe BPK in Bali Province.